Graphene-based materials for photocatalytic and environmental sensing applications - Sujatha Sadana; Natarajan Rajamohan; Rajasimman Manivasagan; Nitin Raut; Santhosh Paramasivam; Gianluca Gatto; Amit Kumar (Results in Engineering)
Graphene Quantum Dots (GQDs) have emerged as promising materials, finding extensive applications in environmental fields such as catalysis, sensors, green fuels, and energy storage. GQDs, a minute segment of graphene smaller than 20 nm in dimension, exhibit electron mobility confinement in all 3D because of their incredible chemical, special structure, electrical, intrinsic, and optical properties. Methods of synthesizing GQDs, including top-down and bottom-up approaches, with a particular emphasis on green synthesis, are discussed. In addition, the review discusses diverse modification strategies aimed at improving the photoluminescence, electrical conductivity, chemical Graphene Quantum Dots (GQDs) have emerged as promising materials, finding extensive applications in environmental fields such as catalysis, sensors, green fuels, and energy storage. GQDs, a minute segment of graphene smaller than 20 nm in dimension, exhibit electron mobility confinement in all 3D because of their incredible chemical, special structure, electrical, intrinsic, and optical properties. Methods of synthesizing GQDs, including top-down and bottom-up approaches, with a particular emphasis on green synthesis, are discussed. In addition, the review discusses diverse modification strategies aimed at improving the photoluminescence, electrical conductivity, chemical and thermal stability, biocompatibility, catalytic performance, and sensing capabilities of graphene quantum dots, thereby enabling their application in bioimaging, sensors, and specific electronic devices. In addition, the review explores the wide-ranging applications of graphene quantum dots, including their roles in sensors, biomedical imaging, drug delivery systems, solar energy conversion, supercapacitors, and battery technologies. The novelty of this review lies in outlining the core principles of photocatalysis with a focus on its applications in environmental remediation, hydrogen evolution and CO₂ conversion. Even though future investigation of GQDs is immense, it is still facing some difficulties in developing as an environmentally friendly process and hence, some significant innovations are required to overcome these difficulties and thermal stability, biocompatibility, catalytic performance, and sensing capabilities of graphene quantum dots, thereby enabling their application in bioimaging, sensors, and specific electronic devices. In addition, the review explores the wide-ranging applications of graphene quantum dots, including their roles in sensors, biomedical imaging, drug delivery systems, solar energy conversion, supercapacitors, and battery technologies. The novelty of this review lies in outlining the core principles of photocatalysis with a focus on its applications in environmental remediation, hydrogen evolution and CO₂ conversion. Even though future investigation of GQDs is immense, it is still facing some difficulties in developing as an environmentally friendly process and hence, some significant innovations are required to overcome these difficulties.